HONEYPOTS AS A PROACTIVE DEFENSE: A COMPARATIVE ANALYSIS WITH TRADITIONAL ANOMALY DETECTION IN MODERN CYBERSECURITY - Karthik Chandrashekar; Vinay Dutt Jangampet , (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2019)
The growing complexity and frequency of cyberattacks require organizations to adopt more robust, flexible, and innovative strategies for intrusion detection. Traditional anomaly or suspicious activity detection mechanisms—often grounded in pattern matching, heuristics, and statistical modeling—suffer from several key shortcomings, including high false-positive rates, susceptibility to evasion by sophisticated adversaries, and insufficient forensic detail for in-depth analysis. These limitations can be particularly problematic when dealing with Advanced Persistent Threats (APTs) that execute stealthy, long-term campaigns aimed at compromising critical infrastructure and exfiltrating sensitive data.Honeypots—purpose-built decoy systems designed to attract malicious actors—have emerged as a powerful, complementary approach that can address many of these gaps. By deliberately enticing attackers, honeypots collect actionable intelligence on adversarial techniques, tactics, and procedures, yielding valuable insights into exploit methods, privilege-escalation paths, and lateral-movement strategies. This proactive engagement goes beyond mere detection: it facilitates real-time observation of threat behaviors, enabling security teams to design more targeted and effective countermeasures.In this paper, we detail the core principles of honeypot deployment and compare their effectiveness with conventional anomaly detection. Our proposed scalable honeypot architecture emphasizes network segmentation, realistic decoy services, thorough logging mechanisms, and automated response orchestration, ensuring that security teams can capture a wide variety of intrusions without jeopardizing production environments. Through a carefully constructed case study, we demonstrate that the incorporation of honeypots substantially enhances detection of both opportunistic and highly sophisticated threats. Notably, our findings underscore reductions in false positives and improved forensic visibility when compared to legacy anomaly-based solutions.We also address essential considerations for sustaining an effective honeypot environment, including risk containment, maintenance overhead, and countermeasures against adversaries who actively probe for deceptive systems. The results of our research confirm that honeypots, when correctly deployed and managed, significantly bolster an organization’s ability to detect emerging threat vectors, gather critical forensic evidence, and respond swiftly, thereby reducing the potential impact of targeted cyberattacks. By providing a more comprehensive, high-fidelity view of malicious activity, honeypots serve as a critical addition to modern cybersecurity defenses, bridging the gap between reactive threat detection and proactive, intelligence-driven security strategies.